2015
DOI: 10.1371/journal.pgen.1005685
|View full text |Cite
|
Sign up to set email alerts
|

Sae2 Function at DNA Double-Strand Breaks Is Bypassed by Dampening Tel1 or Rad53 Activity

Abstract: The MRX complex together with Sae2 initiates resection of DNA double-strand breaks (DSBs) to generate single-stranded DNA (ssDNA) that triggers homologous recombination. The absence of Sae2 not only impairs DSB resection, but also causes prolonged MRX binding at the DSBs that leads to persistent Tel1- and Rad53-dependent DNA damage checkpoint activation and cell cycle arrest. Whether this enhanced checkpoint signaling contributes to the DNA damage sensitivity and/or the resection defect of sae2Δ cells is not k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 66 publications
4
67
0
3
Order By: Relevance
“…While the enrichment of Mre11 at the DSB was comparable in MRE11 and MRE11-NLS cells, less Mre11-NLS was retained at the DSB in the xrs2Δ background at the 1 hr time point ( P <0.05) (Fig 3C). Since Tel1 signaling is abrogated in the xrs2Δ MRE11-NLS mutant, and Tel1 is required for retention of Mre11 at DSBs (Gobbini et al, 2015), we considered the possibility that the Mre11 localization defect in xrs2Δ MRE11-NLS cells could be due to loss of Tel1 recruitment. Indeed, we found that Mre11 enrichment at the HO-induced DSB was the same in MRE11-NLS xrs2Δ and MRE11-NLS cells tel1Δ (Fig 3C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the enrichment of Mre11 at the DSB was comparable in MRE11 and MRE11-NLS cells, less Mre11-NLS was retained at the DSB in the xrs2Δ background at the 1 hr time point ( P <0.05) (Fig 3C). Since Tel1 signaling is abrogated in the xrs2Δ MRE11-NLS mutant, and Tel1 is required for retention of Mre11 at DSBs (Gobbini et al, 2015), we considered the possibility that the Mre11 localization defect in xrs2Δ MRE11-NLS cells could be due to loss of Tel1 recruitment. Indeed, we found that Mre11 enrichment at the HO-induced DSB was the same in MRE11-NLS xrs2Δ and MRE11-NLS cells tel1Δ (Fig 3C).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we found the level of Dna2 enrichment 1 kb from the DSB was not significantly decreased in the MRE11-NLS xrs2Δ strain, despite the decrease in Mre11, whereas Dna2 enrichment was barely above background in MRE11-NLS sae2Δ xrs2Δ cells (Fig 3C). The decreased Dna2 binding in the MRE11-NLS sae2Δ mutant could be due to delayed resection initiation or Rad9 inhibition (Ferrari et al, 2015; Gobbini et al, 2015). We suggest that there are normally two modes of Sgs1-Dna2 recruitment to DSBs: via MRX interaction and by RPA interaction after MRX-Sae2 dependent cleavage creates ssDNA (Fig 3D) (Chen et al, 2013; Shim et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elimination of Rad9 can suppress the sae2Δ resection initiation defect by allowing more efficient recruitment of Dna2-STR to DSBs (Bonetti et al, 2015; Ferrari et al, 2015). Similarly, partial loss of function alleles of TEL1 and RAD53 that reduce Rad9 accumulation at DSBs can also suppress the sae2Δ resection defect (Gobbini et al, 2015). Elimination of Tel1 causes a modest delay in resection initiation while the mec1Δ mutant exhibits increased end resection due to reduced Rad9 recruitment (Clerici et al, 2014; Mantiero et al, 2007).…”
Section: Resection and The Dna Damage Checkpointmentioning
confidence: 99%
“…Such stabilization of Slx4 at DNA lesions, which is also dependent on Rtt107's interaction with phosphorylated H2A (Fig ), is believed to counteract a resection block promoted by Rad9, thereby allowing long‐range resection to occur (Dibitetto et al , ; Liu et al , ). Importantly, the role of Rad9 in counteracting resection relies on its oligomerization and Rad53 signaling (Clerici et al , ; Ferrari et al , ; Gobbini et al , ), which are both dependent on Mec1‐mediated phosphorylation events. Therefore, Mec1 plays opposing roles in HR, inhibiting resection via the Rad9–Rad53 signaling axis or promoting resection by mediating the Slx4–Dpb11 interaction (Fig ).…”
Section: Introductionmentioning
confidence: 99%